Potential of natamycin to control growth of Zygosaccharomyces spp. in apple juice during storage - Karaman, Kevser; Sagdic, Osman; Yilmaz, Mustafa Tahsin (ELSEVIER, 2020)
In this research, anti-yeast activity of natamycin in apple juice inoculated with both Zygosaccharomyces rouxii and Z. bailii during the storage at different temperatures was investigated. For this purpose, a response surface methodology approach was used to test and optimize effects of some processing variables; storage time (1, 21 and 41 days), storage temperature (4, 12 and 20 degrees C), sodium benzoate as a positive control (0, 0.05 and 0.1%) and natamycin concentration (0, 30 and 60 mg/L) on several physicochemical and bioactive properties of the apple juice samples. The results showed that the natamycin performed a remarkable anti-yeast effect on Z. bailii rather than on Z. rouxii. The brix levels of the samples decreased and so the turbidity values increased significantly due to the yeast activity during the storage. Bioactive properties were also significantly affected by the natamycin which was also revealed to increase the antioxidant capacity of apple juice during storage. Using multiple response optimization technique, it was calculated that minimum yeast count (YC) values would occur at storage time = 38.64 and 40.9 days, storage temperature = 19.81 and 14.4 degrees C, sodium benzoate level (fixed to 0%) and natamycin concentration = 40 and 51.9 mg/L for the samples inoculated with Z. bailii and Z. rouxii, respectively. It was concluded that the bioactive properties of apple juice could be preserved by addition of natamycin which is suggested to be a natural inhibitor during the storage.
Keywords: Zygosaccharomyces spp.; Natamycin; Apple juice; Antifungal activity; Response surface methodology; ANTIOXIDANT ACTIVITY; SPOILAGE YEASTS; BAILII; PARAMETERS; ROUXII; OPTIMIZATION; Food Science & Technology; Microbiology